PERSEPSI DOSEN FAKULTAS SYARI’AH DAN HUKUM UIN RADEN FATAH PALEMBANG TERHADAP PRAKTEK PEMBULATAN HARGA DARI TOTAL BELANJA KONSUMEN DI TOKO SWALAYAN - Sanata, Alfan; Nilawati, Nilawati; Gibtiah, Gibtiah (Muamalah, 2018)
ABSTRACT This research entitled Perception of Syari'ah Faculty Lecturers and Law of UIN Raden Fatah Palembang Against the Practice of Rounding Prices from Total Consumer Expenditures at Supermarkets. This research is motivated by the practice of price rounding that occurs in supermarkets. The practice of rounding prices seems to only benefit one party because it is done without an agreement between the two parties. Two things were raised as the focus of the research. First, what was the Perception of the Lecturers of the Faculty of Sharia and the Law of UIN Raden Fatah Palembang on the Practice of Rounding Prices of Total Consumer Expenditures at Supermarkets. Second, What is the Legal Basis Used by Lecturers of the Sharia Faculty and Law of UIN Raden Fatah Palembang Against the Practice of Rounding Prices from Total Consumer Expenditures at Supermarkets. This research is a field research (Field Research), which is located in the Faculty of Syari'ah and the Law of UIN Raden Fatah Palembang. The method of data collection in this study is through interviews and literature. as primary data obtained from interviews with the Syari'ah Faculty Lecturers and the Law of UIN Raden Fatah Palembang. While secondary data is data obtained from books and research results related to the practice of rounding prices. after the data is obtained, then it is analyzed using qualitative descriptive techniques. From the descriptions presented by various reviews, the authors conclude that the perceptions of the Shari'ah faculty lecturers and the law of raden fatah regarding the practice of rounding prices of total consumer spending in supermarkets must be in accordance with the rules that apply in Islamic teachings. The legal basis that is suitable for use by lecturers is QS. An-Nisa ': 29, which is a strict prohibition on a believer who eats up the wealth of others with a physical path, except in trading on the basis of liking. And QS. Al-Maidah: 38 "assariqu wassariqatu faqtha’u aidiyahuma" that if a man or woman steals, then cut off his second hand.